From Synaptic Protein to Prion: The Long and Controversial Journey of α-Synuclein - Heras-Garvin, Antonio; Stefanova, Nadia (Frontiers in Synaptic Neuroscience, 2020)
Since its discovery 30 years ago, α-synuclein has been one of the most studied proteins in the field of neuroscience. Dozens of groups worldwide have tried to reveal not only its role in the CNS but also in other organs. α-synuclein has been linked to several processes essential in brain homeostasis such as neurotransmitter release, synaptic function and plasticity. However, despite the efforts made in this direction, the main function of α-synuclein is still unknown. Moreover, α-synuclein became a protein of interest for neurologist and neuroscientist when mutations in its gene were found associated with Parkinson’s disease and even more when α-synuclein protein deposits were observed in the brain of Parkinson’s disease, dementia with Lewy bodies and multiple system atrophy patients. At present, the abnormal accumulation of α-synuclein constitutes one of the pathological hallmarks of these disorders, also referred as α-synucleinopathies, and it is used for post-mortem diagnostic criteria. Whether α-synuclein aggregation is cause or consequence of the pathogenic events underlying α-synucleionopathies remains unclear and under discussion. Recently, different in vitro and in vivo studies have shown the ability of pathogenic α-synuclein to spread between cells, not only within the CNS but also from peripheral locations such as gut, salivary glands and through the olfactory network into the CNS, inducing abnormal misfolding of endogenous α-synuclein and leading to neurodegeneration and motor and cognitive impairment in animal models. Thus, it has been suggested that α-synuclein should be considered a prion protein. Here we present an update of what we know about α-synuclein function, aggregation and spreading, and its role in neurodegeneration. We also discuss the rationale and findings supporting the hypothetical prion nature of α-synuclein, its weaknesses and future perspectives for research and the development of disease-modifying therapies.